2005
DOI: 10.1094/pd-89-1317
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal Improvement of a Powder Formulation of Penicillium oxalicum, a Biocontrol Agent of Tomato Wilt

Abstract: Sugars, polyalcohols, inorganic salts, and detergents were added to conidia of Penicillium oxalicum at three different points of the production-formulation process to improve water dispersal. Effects also were tested on conidial germination and production. Conidial germination without additives ranged from 51 to 79%. Additives did not reduce conidial germination except for 50% polyethylene glycol (PEG) 300 and 10% CaCl2. Sunflower oil and sodium alginate, sucrose (0.5, 15, 30, and 60%), D-sorbitol (30 and 60%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Moreover, Tween 80 is a detergent and enhances bacterial dispersion in plant surfaces and helps to reduce surface tension at the liquid-solid interface, facilitating air distribution. Notably, Tween 80 is used as an adjuvant in the formulation of several biopesticides (2,17,31). Following a single field application during bloom, EPS62e colonized blossoms and reached population levels near the carrying capacity of apple and pear flowers (6,24,25); this behavior on blossoms is similar to that of other biocontrol agents of fire blight (16,27,37) that efficiently colonize blossoms when phenoclimatic conditions during spring are optimal (14).…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, Tween 80 is a detergent and enhances bacterial dispersion in plant surfaces and helps to reduce surface tension at the liquid-solid interface, facilitating air distribution. Notably, Tween 80 is used as an adjuvant in the formulation of several biopesticides (2,17,31). Following a single field application during bloom, EPS62e colonized blossoms and reached population levels near the carrying capacity of apple and pear flowers (6,24,25); this behavior on blossoms is similar to that of other biocontrol agents of fire blight (16,27,37) that efficiently colonize blossoms when phenoclimatic conditions during spring are optimal (14).…”
Section: Discussionmentioning
confidence: 89%
“…Because all the tested plants in the different treatments were healthy, the healthy plants in high disease incidence treatments contained more relative abundances of the rhizospheric genera Ralstonia and Fusarium, increasing the risk of plant illness (Wei et al 2011;Shanmugam et al 2015). Moreover, studies have confirmed that the genera Bacillus (Singh and Siddiqui 2015), Penicillium (Sabuquillo et al 2006), and Trichoderma (Blaya et al 2013) act as biocontrol agents could induce a resistance capacity of plants that provides protection against of the microbial pathogens (Ent et al 2009). Pseudomonas was reported to suppress plant disease in several studies (Dowling and O'Gara 1994;Singh and Siddiqui 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, P. oxalicum was shown able to induce resistance in tomato plants inoculated with F. oxysporum f. sp. lycopersici [54]. Also, Qiu et al [55] have isolated from Ginkgo biloba L. twigs A. nidulans and A. oryzae which were able to produce phenolic and flavonoid compounds.…”
Section: Discussionmentioning
confidence: 99%